1998
DOI: 10.1590/s0074-02761998000500011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Den-2 Virus In Brazil

Abstract: Dengue (DEN) viruses belong to the family Flaviviridae, genus Flavivirus, and occur as four antigenically related, but distinct serotypes designated DEN-1, 2, 3 and 4 (EG Westaway et al. 1985 Intervirology 24: 183-192). The viruses are characterized by a single strand of RNA associated with a core protein, in a nucleocapside surrounded by a lipid envelope. The genoma consist of a single open reading frame coding for core protein (C), precursor of the membrane protein (prM) and envelope (E) structural proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
6
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
5
6
0
2
Order By: Relevance
“…These data corroborate the results previously obtained by the partial sequencing of different genomic fragments (Deubel et al 1993, RicoHesse et al 1997, Miagostovich et al 1998. A direct association between the introduction of Asian DEN-2 virus with severe disease in the Americas has been shown previously (Rico-Hesse et al 1997), and our results are consistent with this scenario.…”
Section: Discussionsupporting
confidence: 94%
“…These data corroborate the results previously obtained by the partial sequencing of different genomic fragments (Deubel et al 1993, RicoHesse et al 1997, Miagostovich et al 1998. A direct association between the introduction of Asian DEN-2 virus with severe disease in the Americas has been shown previously (Rico-Hesse et al 1997), and our results are consistent with this scenario.…”
Section: Discussionsupporting
confidence: 94%
“…Subsequently, in 1986, the first outbreak of greater proportions caused by DEN-1 occurred in the met-and Alagoas classified them into the Asian/ American-Asian genotype (18). Similar results were also obtained by nucleotide sequence analysis of another E protein gene segment (nucleotides 85 to 282) of three DEN-2 samples isolated in Brazil in 1990 (7).…”
Section: Discussionsupporting
confidence: 65%
“…Rico-Hesse et al (16) analyzed two DEN-2 viruses isolated in Venezuela and Colombia some time around 1987, and concluded that they belonged to the Southeast Asian genotype. In Brazil, this genotype was probably introduced either at the same time or at some point during 1988, like in other areas of the Americas (6,8,16,18,20,38,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1,832,371 cases were reported, resulting from DEN-1 and/or DEN-2 epidemics, and occurred in 24 out of 26 states and the Federal District/Brasília (Ministry of Health, Brazil). Molecular analysis performed on genome fragments from DEN-1 and DEN-2 viruses identified the Caribbean and Jamaican genotypes, respectively, as the virus strains circulating in the country (Rico-Hesse 1990, Vorndam et al 1994, Miagostovich et al 1998). The Jamaica genotype introduction into the Americas resulted in both an increase in the severe forms of the disease and epidemics in which there were a significant number of DHF/DSS cases (Nogueira et al 1993, RicoHesse et al 1997 .…”
mentioning
confidence: 99%